Classification of health indicators affecting human development index: a cross-country study - Nasrin Hozarmoghadam; Bahram Sahabi; Ali Mohammad Ahmadi; Vahid Mahmoudi (Gonabad University of Medical Sciences, 2017)
The health dimension of Human Development Index (HDI) is currently assessed by life expectancy at Birth. In this regard, the question is whether or not the life expectancy indicator merely can explain the health status of countries. Accordingly, the aim of this study was to determine and classify health indicators affecting human development index. For this purpose, 70 countries were selected as cases, and 27 health indicators were determined as variables. The data were gathered from 2000 to 2012 and analyzed using R-type factor analysis technique within the principal components in software. Based on the obtained results from factor analysis, the examined variables were classified into six main factors including "manageable diseases", "serious diseases", "environmental factors", "quality of health care", "disease preventive services", and "public health expenditure" that explained 73% of the total variance. This finding indicates the deep effect of these six main factors on health status of a community. So, it can be argued that health development description is not limited to the life expectancy Index. Instead, it is affected by many factors including diseases, health services, health care costs, and environmental factors. Therefore, life expectancy cannot be a comprehensive indicator of health sector in HDI and the current understanding in this regard should be revised.